2018
DOI: 10.1177/2054358118801589
|View full text |Cite
|
Sign up to set email alerts
|

Updated Canadian Expert Consensus on Assessing Risk of Disease Progression and Pharmacological Management of Autosomal Dominant Polycystic Kidney Disease

Abstract: Purpose:The purpose of this article is to update the previously published consensus recommendations from March 2017 discussing the optimal management of adult patients with autosomal dominant polycystic kidney disease (ADPKD). This document focuses on recent developments in genetic testing, renal imaging, assessment of risk regarding disease progression, and pharmacological treatment options for ADPKD.Sources of information:Published literature was searched in PubMed, the Cochrane Library, and Google Scholar t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 66 publications
1
41
0
1
Order By: Relevance
“…A small, single-center study from Edwards and colleagues 4 addressed this concern and demonstrated the sustained efficacy of tolvaptan in slowing the loss of GFR by w1 ml/ min per 1.73 m 2 per year for up to 11.2 years (average follow-up, 4.6 years). In order to understand the impact of tolvaptan in delaying ESRD, we estimated the potential benefit of tolvaptan for patients who are considered eligible to receive tolvaptan by expert guidelines or consensus publications [5][6][7] ; that is, individuals aged 55 years or younger, with a Mayo imaging class of 1C, 1D, or 1E. We did not consider individuals older than age 55 years or those with Mayo imaging classes of 1A, 1B, or 2, who would be considered to have low risk of rapid progression.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A small, single-center study from Edwards and colleagues 4 addressed this concern and demonstrated the sustained efficacy of tolvaptan in slowing the loss of GFR by w1 ml/ min per 1.73 m 2 per year for up to 11.2 years (average follow-up, 4.6 years). In order to understand the impact of tolvaptan in delaying ESRD, we estimated the potential benefit of tolvaptan for patients who are considered eligible to receive tolvaptan by expert guidelines or consensus publications [5][6][7] ; that is, individuals aged 55 years or younger, with a Mayo imaging class of 1C, 1D, or 1E. We did not consider individuals older than age 55 years or those with Mayo imaging classes of 1A, 1B, or 2, who would be considered to have low risk of rapid progression.…”
mentioning
confidence: 99%
“…12 This result has been incorporated into some clinical guidelines for the use of tolvaptan, which suggest that maintenance of urine osmolality below 280-300 mOsm/kg is adequate. 5,6 Aquaresis and vasopressin levels also can be decreased with reduction of dietary solute (protein and salt). 13 Therapy for chronic medical conditions commonly managed by nephrologists, such as hypertension, diabetes, and fluid overload due to chronic kidney disease or nephrotic syndrome, requires the patient and nephrologist to accept years of treatment and possible treatment-associated side effects in the expectation of a clinical benefit.…”
mentioning
confidence: 99%
“…Although our sample size precluded statistical comparisons between the methods, the Mayo ellipsoid tended to have the best performance in terms of accuracy and variability, which further supports the use of this already commonly used method. A barrier to the adoption of TKV measurements is the time required for the manual planimetry method (7,10,11); similar to prior publications, the interpreting radiologists performed ellipsoid measurements in a fraction of the time required for planimetry.…”
Section: Discussionmentioning
confidence: 95%
“…Inhibition of the renin-angiotensin-aldosterone system and aggressive blood pressure control (< 110/75 mm Hg) should be considered in patients with autosomal dominant polycystic kidney disease who are younger than 50 years and have preserved kidney function. 3 Cyst infections should be treated with cyst-penetrating antibiotics (i.e., fluoroquinolone) for a minimum of two to four weeks, and possible cyst drainage. 4 Chronic abdominal discomfort is common and acute-on-chronic pain secondary to cyst hemorrhage or nephrolithiasis can occur.…”
Section: Supportive Care Includes Management Of Hypertension Infectimentioning
confidence: 99%
“…cmaj.ca/lookup/suppl/doi:10.1503/cmaj.170443/-/DC1) with preserved kidney function, with benefit balanced by cost, aquaretic adverse effects and potential hepatotoxicity. 3 PRACTICE | FIVE THINGS TO KNOW ABOUT ...…”
Section: Patients With Autosomal Dominant Polycystic Kidney Disease Smentioning
confidence: 99%